Pakistan : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
The Madagascar Poverty Reduction Strategy Paper (PRSP) includes detailed description of poverty developments and the profile of the poor. The diagnostic section shows that the rural poor largely depend on agriculture, especially the production of rice. The IMF staff especially commends the PRSP for incorporating community preferences and listing the vulnerabilities of the population. The staff supports the main thrust of the Madagascar Poverty Reduction Strategy with its focus on governance, inclusive growth, and service delivery for human and material security. Madagascar has embarked on a three-year macroeconomic program (2001-04).